Evaluasi Program Pesantren Ramah Anak Model CIPP di Provinsi Sumatera Barat - Natsir, Albert; Zulmuqim, Zulmuqim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractThis study describes the results of the evaluation of the child-friendly pesantren programme in West Sumatra Province. The model used is CIPP with Mixed Method. Data collection techniques used questionnaires, observation sheets, interviews, concept mastery tests and child-friendly pesantren guidelines. Data analysis and programme evaluation procedures are described in this article.Â The results of the context evaluation showed that violence, discrimination and harassment still occur in most Islamic boarding schools in West Sumatra province. The results of the input evaluation showed that the child-friendly pesantren program guidelines issued by the Ministry of Religious Affairs, the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia have not been optimally socialised and the pesantren leaders, board of asatidz, santri and the community are aware of the child-friendly pesantren program but do not understand the concept, guidelines and technical instructions for child-friendly pesantren. The results of the process evaluation, namely monitoring designed to reveal the strengths and weaknesses of the implementation of the child-friendly pesantren programme, have not been optimal. Not all pesantren have a child-friendly pesantren development team. For pesantren that already have a child-friendly pesantren team, the team members do not have relevant competencies. The evaluation of products or outputs and outcomes designed to assess programme outcomes and programme sustainability shows that the child-friendly pesantren programme launched and developed by the government and Islamic boarding schools has not run as expected.AbstrakPenelitian ini menjelaskan tentang hasil evaluasiprogram pesantren ramah anak di Provinsi Sumatera Barat.Model yang digunakanCIPP dengan metode Mixed Method. Teknik pengumpulan data menggunakan angket, lembar observasi, wawancara, tespenguasaan konsep dan pedoman pesantren ramah anak. Analisis data dan prosedur evaluasi program dijelaskan dalam artikel ini.Â Sampel penelitian adalah 23 pondok pesantren yang tersebar di 12 kabupaten kota di Provinsi Sumatera Barat.Hasil evaluasi konteks menunjukkan bahwa masih terjadi kekerasan, diskriminasi dan pelecehan di rata rata pondok pesantren di provinsi Sumatera Barat. Hasil evaluasi inputÂ menunjukkan bahwa pedoman program pesantren ramah anak yang diterbitkan oleh Kementerian Agama, Kementerian Pemberdayaan Perempuan dan Perlindungan Anak Republik Indonesia belum optimal disosialisasikan dan pimpinan pesantren,dewan asatidz,santri dan masyarakat mengetahui adanya program pesantren ramah anak tetapi belum memahami konsep, panduan dan petunjuk teknis pesantren ramah anak. Hasil evaluasi proses, yaitu monitoring yang dirancang untuk mengungkap kekuatan dan kelemahan pelaksanaan program pesantren ramah anak belum optimal. Belum semua pondok pesantren memiliki tim pengembang pesantren ramah anak. Bagi pesantren yang telah memiliki tim pesantren ramah anak, anggota tim belum memiliki kompetensi yang relevan. Evaluasi produk atau keluaran dan hasil yang dirancang untuk menilai hasil programdan keberlanjutan program menunjukkan bahwa program pesantren ramah anak yang diluncurkan dan dikembangan oleh pemerintah dan pondok pesantren belum berjalan seperti yang diharapkan.